THE IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE IN FOREIGN LANGUAGE TEACHING - Zakirova Shaxzoda Nodirjon qizi (Western European Studies, 2024)
This article explores the integral role of Artificial Intelligence in modern education. It discusses how ICT has revolutionized access to information, transformed learning environments, personalized learning experiences, facilitated collaboration, connected global learning communities, supported teacher professional development, enhanced administrative efficiency, and promoted lifelong learning. By leveraging AI and ICT tools and technologies, education can become more inclusive, interactive, and innovative, preparing learners for success in the digital age
Keywords: collaborative; ICT; modern education